Kualitas Hidup Mantan Penyalahguna Narkoba Pasca Relapse - Wardani, Arlita Lusiana; Suryanto, Suryanto (CV. ULIL ALBAB CORP, 2026)
This study aimed to understand the quality of life of former drug abusers after relapse and the factors that influence their post-relapse quality of life. This study used a qualitative approach with an intrinsic case study design. The research participants were two former drug abusers who had relapsed more than once and, at the time of the study, had not used drugs for more than six months. Data were collected through guided free interviews. The results showed that the participants experienced a decline in their physical condition, marked by sleep disorders and other health problems. Psychologically, they still experienced stress due to family issues but tried to accept themselves and remain grateful. In terms of social relationships, they tried to reject and avoid friends who used drugs by blocking their WhatsApp numbers and other social media accounts. Additionally, to overcome feelings of loneliness, they participated in community activities, joined social and other community groups, and attempted to maintain good relationships with their families, even though some issues remained unresolved. Regarding their environment, they did not have genuine friends and were still surrounded by peers who encouraged drug use; they were unwilling to use health facilities and diverted their drug use by drinking alcohol with their friends. The factors influencing quality of life included age, marital status, and family. Other emerging themes included hopes for a better life, a desire to benefit others, and the maintenance of their recovery. This research provides an in-depth understanding of the quality of life of former drug abusers after relapse, which may be useful for developing more effective rehabilitation and support programs for them.